2018
DOI: 10.1002/aenm.201801032
|View full text |Cite
|
Sign up to set email alerts
|

Toward Predicting Efficiency of Organic Solar Cells via Machine Learning and Improved Descriptors

Abstract: include the strong electron-electron interactions and strong electron-phonon couplings as well as the complicated donor/ acceptor (D/A) interface morphology, which are fundamentally different from inorganic semiconductors. [23,24] Therefore, the accurate simulating of OPVs requires high-level theoretical methods in quantum chemistry, quantum dynamics and statistical mechanics, and in recent years there have been substantial progress for the theoretical understanding of many microscopic processes such as charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
220
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(238 citation statements)
references
References 96 publications
(237 reference statements)
6
220
0
Order By: Relevance
“…For example, the coefficients in simple linear regression model as well as the logistic regression can provide an indication of the relative importance of different features. Feature importance analysis in tree‐based models has been routinely used to assess the important physical parameters that are related to the predictive targets . For deep learning‐based models, visualizing the hidden layer activations has been found to give interpretable chemical intuition and accurate mapping of structural space .…”
Section: Model Selection and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the coefficients in simple linear regression model as well as the logistic regression can provide an indication of the relative importance of different features. Feature importance analysis in tree‐based models has been routinely used to assess the important physical parameters that are related to the predictive targets . For deep learning‐based models, visualizing the hidden layer activations has been found to give interpretable chemical intuition and accurate mapping of structural space .…”
Section: Model Selection and Trainingmentioning
confidence: 99%
“…While the Scharber model is widely used for computing SCE, Sahu et al have realized, from a data set of 280 small molecule OPV systems, that for all high‐performance devices, frontier orbitals of donor molecules are nearly degenerated and therefore orbitals other than just HOMO and LUMO should be considered. The authors considered 13 quantum‐mechanical descriptors including 1) number of unsaturated atoms in the main conjugation path of donor molecules(NatomD), 2) polarizability of donor molecules, 3) the energetic differences of LUMO and LUMO+1 of donor molecules (Δ L ), 4) the energetic differences of HOMO and HOMO−1 of donor molecules(Δ H ), 5) vertical ionization potential of donor molecules (IP(ν)), 6) reorganization energy for holes in donor molecules (λ h ), 7) hole–electron binding energy in donor molecules( E bind ), 8) the energetic difference of LUMO of donor and LUMO of acceptor(ELLDA), 9) the energetic difference of HOMO of donor and LUMO of acceptor(EHLDA), 10) energy of the electronic transition to a singlet excited state with the largest oscillator strength( E g ), 11) change in dipole moment in going from the ground state to the first excited state for donor molecules(Δ ge ), 12) energy of the electronic transition to the lowest‐lying triplet state(ET1), and 13) the energetic difference of LUMO and LUMO+1 of acceptors (normalΔLA).…”
Section: Applicationmentioning
confidence: 99%
“…Recently, machine‐learning technologies have revolutionized the solar energy fields and played an important role in designing the optoelectronic materials and predicting OSC performances. Previous studies demonstrated that the machine‐learning approaches (e.g., Gaussian processes regression, gradient‐boosting regression tree, artificial neural network, and Random Forest regression) can be used to investigate the relationship between machine‐learning predicted and experimental measured (or density functional theory calculated) PCE values for electronic and device properties of OSCs . To discover efficient photovoltaic materials, machine‐learning‐assisted technology has been used for designing promising molecules and screening conjugated polymers for OSCs .…”
Section: Comparison Of Prediction and Measurement Results Of Tandem Oscsmentioning
confidence: 99%
“…Previous studies demonstrated that the machine-learning approaches (e.g., Gaussian processes regression, gradientboosting regression tree, artificial neural network, and Random Forest regression) can be used to investigate the relationship between machine-learning predicted and experimental measured (or density functional theory calculated) PCE values for electronic and device properties of OSCs. [18][19][20][21] To discover…”
mentioning
confidence: 99%
“…The RMSE of Random Forest is 2.13, for cross-validated mean, 1.91, for test set. [27] As discussed in the principles of charge transportation in OFETs, [30] molecular frontier energies of n-type materials in the n-type OFETs play a crucial role in effective electrons injection, as the electron mobility can be optimized by reducing small electron injection barrier height. The Gradient Boosting model also has performance with RMSE of 2.36 and 2.33 for cross-validated train set and test set, which is insufficient for practical use.…”
mentioning
confidence: 99%